2013
DOI: 10.5152/akd.2013.136
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of standard Euroscore, logistic Euroscore and Euroscore II in prediction of early mortality following coronary artery bypass grafting

Abstract: Objective: EuroSCORE is the most widely used risk prediction system. Standard EuroSCORE which had been published in 1999, was revised as a Logistic EuroSCORE in 2003. Further it was reconsidered and published as EuroSCORE II in 2011. In this study we compared Standard, Logistic EuroSCORE and EuroSCORE II in prediction of early mortality following coronary artery bypass grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The mortality rate in our study was at the level of 5.21% and it did not differ with the background of other similar studies, in which this value ranged from 2.2% to 5.66% [8][9][10][11][12][13]. For our CABG patients, this value was 5.33%.…”
Section: Discriminatory Powersupporting
confidence: 55%
See 1 more Smart Citation
“…The mortality rate in our study was at the level of 5.21% and it did not differ with the background of other similar studies, in which this value ranged from 2.2% to 5.66% [8][9][10][11][12][13]. For our CABG patients, this value was 5.33%.…”
Section: Discriminatory Powersupporting
confidence: 55%
“…The differences between AUC of addES and the AUC of ESII in both examined groups were statistically significant (Table 4). In contrast to this data, the addES remained good in three studies performed by Kunt et al [9], Toumpoulis et al [17], and in a CABG cohort from Akgül et al [11]: AUC: 0.70 and 0.72, 0.992, respectively.…”
Section: Discriminatory Powermentioning
confidence: 52%
“…Also Akgul et al . reported a good C-statistic value of EuroSCORE II compared to the original EuroSCORE (0.992 [95% CI: 0.977-0.998] for logistic EuroSCORE and 0.990 [95% CI: 0.975-0.997] for EuroSCORE II) and in the subgroup of high risk (additive EuroSCORE > 6) they found that again EuroSCORE II was better (0.857 [95% CI: 0.691-0.954] for logistic EuroSCORE and 0.961 [95% CI: 0.829-0.998] for EuroSCORE II) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%